2011
DOI: 10.1371/journal.pone.0019575
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous Dysfunction in Hamsters Infected with West Nile Virus

Abstract: Clinical studies and case reports clearly document that West Nile virus (WNV) can cause respiratory and gastrointestinal (GI) complications. Other functions controlled by the autonomic nervous system may also be directly affected by WNV, such as bladder and cardiac functions. To investigate how WNV can cause autonomic dysfunctions, we focused on the cardiac and GI dysfunctions of rodents infected with WNV. Infected hamsters had distension of the stomach and intestines at day 9 after viral challenge. GI motilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 59 publications
(99 reference statements)
2
31
0
Order By: Relevance
“…Additional studies using electromyography in WNV-inoculated hamsters have also provided correlations between autonomic dysfunction related to respiratory distress [112] and gastrointestinal [185] symptoms following WNV infection related to peripheral neuronal infection. This model has thus provided much insight not only into neuroinvasive mechanisms of flaviviruses but also into subsequent pathological manifestations that can be attributed to motor neuron infection, death and viral persistence.…”
Section: Hamster Model For Flavivirus Neuroinvasive Diseasementioning
confidence: 99%
“…Additional studies using electromyography in WNV-inoculated hamsters have also provided correlations between autonomic dysfunction related to respiratory distress [112] and gastrointestinal [185] symptoms following WNV infection related to peripheral neuronal infection. This model has thus provided much insight not only into neuroinvasive mechanisms of flaviviruses but also into subsequent pathological manifestations that can be attributed to motor neuron infection, death and viral persistence.…”
Section: Hamster Model For Flavivirus Neuroinvasive Diseasementioning
confidence: 99%
“…described autonomic symptoms, for example, distension of stomach and intestines and a reduction in the HRV, in an experimental model of hamsters infected with West Nile virus (Wang et al. 2011). Histopathological analysis in this model revealed that neuronal structures relevant for the ANS, that is, neurons in the brain stem, myenteric neurons, and cells in the sinoatrial and atrioventricular nodes were infected with West Nile virus.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies 27,46 seeking to find neurological explanations for the respiratory, gastrointestinal, bladder, and cardiac dysfunction found in some humans with WNV infection used WNV-infected hamsters, which, like mice, 21 show gastric and intestinal distension. They found by electromyograph (EMG) electrophysiological suppression of the diaphragm either directly due to WNV-infected neurons found by immunostaining in the brainstem and mid-cervical spinal cord or indirectly via altered vagal afferent function.…”
Section: Discussionmentioning
confidence: 99%